2022
DOI: 10.3389/fmed.2022.853941
|View full text |Cite
|
Sign up to set email alerts
|

Circulating D-Dimers Increase the Risk of Mortality and Venous Thromboembolism in Patients With Lung Cancer: A Systematic Analysis Combined With External Validation

Abstract: BackgroundD-dimer is a fibrin-degrading substance that is soluble and whose degradation is produced by plasma protein-mediated degradation of cross-linked fibrin. Previous investigations have shown a link between D-dimer and the mortality in lung cancer patients. However, different investigations varied whether D-dimer could predict prognosis in these patients.MethodsA meta-analysis and systematic review of all available cohort studies were performed on the link between circulating D-dimer levels and survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
(73 reference statements)
2
8
0
Order By: Relevance
“…In the present study VTE showed a statistically significant association with high D dimer (ng/ml), sPselectin (ng/ml), Khorana score, and Vienna CATS score. This is in similarity to Li et al (22) who reported that VTE showed a statistically significant association with high D dimer (P<0.05), but contrary to Hayashida et al (23) who found that D-dimer levels were not associated with VTE in the multivariate analysis, likely because they are affected by many risk factors, such as cancer and aging.…”
supporting
confidence: 86%
“…In the present study VTE showed a statistically significant association with high D dimer (ng/ml), sPselectin (ng/ml), Khorana score, and Vienna CATS score. This is in similarity to Li et al (22) who reported that VTE showed a statistically significant association with high D dimer (P<0.05), but contrary to Hayashida et al (23) who found that D-dimer levels were not associated with VTE in the multivariate analysis, likely because they are affected by many risk factors, such as cancer and aging.…”
supporting
confidence: 86%
“…According to the results of the meta-analyses carried out by Jean-François Llitjos et al and Li J et al, high D-dimer was found to be a major risk factor for DVT and that patients at high risk of DVT are more likely to be admitted to the intensive care unit [40,41]. This could be due to a syndrome of systemic inflammatory response to activation of blood coagulation, defined as a high level of fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, although D-dimer has been reported as a prognostic indicator for patients with PC, its clinical application remains controversial due to the limited size of the studies and the lack of adjustment for risk factors 11 . In these meta-analyses, D-dimer has been shown to predict poor prognosis in lung, breast and gastric cancers [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%